The relevance of subtyping children with mathematical learning disabilities. (September 2020) - Huijsmans, Marije D.E.; Kleemans, Tijs; van der Ven, Sanne H.G.; Kroesbergen, Evelyn H.
Highlights: Different profiles of mathematics performance have been theorized in the literature. The present study empirically identified one generally low-achieving profile. Specific profiles of mathematical learning disabilities were not identified. Individual variation was too large for a meaningful distinction between profiles. Heterogeneity in math performance should therefore be acknowledged. Abstract: Background: Profiles of mathematical learning disability (MLD) have been conceptualized in the literature, but empirical evidence to support them based on academic and cognitive characteristics is lacking. Aims: We examined whether profiles of mathematics performance can empirically be identified and whether the identified profiles also differ in underlying cognitive skills. Methods and Procedures: Latent profile analysis in 281 fourth-graders. Basic arithmetic and advanced mathematics were used to identify profiles. Cognitive skills were then described for each profile of mathematics performance. Outcomes and Results: Four profiles of mathematics performance were retrieved from the data, including one general low-achieving profile. Additional profiles of MLD were not found, possibly because individual variation was substantial. Conclusions and Implications: It is highly important to understand children's mathematics performance from an individual perspective, rather than by averaging these children over subgroups. These new insights can be used to better tend to the specific needs of children with mathematical difficulties.